Uso do potencial evocado auditivo de média latência em populações infantis: uma revisão integrativa - Romero, Ana Carla Leite; Oliveira, Anna Caroline Silva De; Regaçone, Simone Fiuza; Frizzo, Ana Cláudia Figueiredo (ABRAMO Associação Brasileira de Motricidade Orofacial, 2016)
ABSTRACT This study aimed to investigate, in the literature, the use of middle latency auditory evoked potentials in children to study the auditory system in its normal and deviant processes. The integrative scientific literature review consisted of searching studies using PubMed, Scopus and Scielo databases. The search terms descriptors were: auditory middle latency response , auditory middle latency potential, children, child, childhood, maturation and development. The selected studies were full papers whose participants were children who underwent middle latency auditory evoked potentials exams. The analysis of the studies, individually, verified aspects related to the aim of the research, the methodology used and the conclusion of each study. A total of 11 studies retrieved from PubMed, eight from Scpus and two studies from Scielo were selected and read in full. Out of the 21 articles, six investigations had been carried out with healthy children, four of them examined the components of this potential in children with language disorders or specific language disorders, four studies assessed children with cochlear implants and seven investigations with children with other changes. This integrative review showed the importance of research of Middle Latency Auditory Evoked Potentials in children. Such an assessment has allowed earlier and accurate diagnosis of patients with language, speech or learning disorders as well as auditory processing disorders, in addition to monitoring therapeutic evolution.

RESUMO Este estudo teve como objetivo investigar na literatura a utilidade do Potencial evocado auditivo de média latência na população infantil para o estudo do sistema auditivo em seus processos normais e desviantes. A revisão integrativa da literatura científica consistiu na busca de estudos utilizando as bases de dados: PubMed, Scopus e Scielo. Como descritores para a pesquisa foram utilizados os termos: auditory middle latency response auditory middle latency potential , children, child, childhood, maturation' e development. Os estudos eram artigos completos, cujos participantes foram crianças, submetidas ao exame de Potencial evocado auditivo de média latência. A análise dos estudos individualmente verificou aspectos relacionados ao objetivo da pesquisa, a metodologia utilizada e a conclusão de cada estudo. Foram selecionados e lidos na íntegra um total de 11 estudos da base bibliográfica PubMed, oito estudos da Scopus e dois estudos da Scielo. Do total de 21 artigos, seis deles foram realizados com crianças saudáveis, quatro examinaram os componentes desse potencial em crianças com distúrbio de linguagem ou distúrbio específico de linguagem, quatro estudos avaliaram crianças usuárias de implante coclear, e sete crianças com outras alterações. Esta revisão integrativa mostrou a importância da investigação dos potenciais evocados auditivos de média latência em crianças. Tal avaliação vem permitindo um diagnóstico mais precoce e preciso de pacientes com alterações de linguagem, fala ou de aprendizado e de distúrbios do processamento auditivo além do monitoramento de evolução terapêutica.
Use of middle latency auditory evoked potentials in children: an integrative review
Keywords: Child; Child Development; Evoked Potentials, Auditory; Hearing; Hearing Tests; Criança; Desenvolvimento Infantil; Potenciais Evocados Auditivos; Audição; Testes auditivos